1999
DOI: 10.1086/315011
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 Produced by Macrophages Inoculated withMycobacterium aviumAttenuates Mycobacteria‐Induced Apoptosis by Reduction of TNF‐α Activity

Abstract: Normal human macrophages respond to infection with Mycobacterium avium, serovar 4, by producing tumor necrosis factor (TNF)-alpha, which mediates apoptosis, and by elaborating interleukin (IL)-10, a TNF-alpha antagonist. We show that IL-10 down-regulates apoptosis by inhibiting the TNF-alpha production of the inoculated macrophages and by inducing the release of soluble TNF receptor type 2 from the macrophages, which leads to inactivation of TNF-alpha. These experiments suggest that induction of IL-10 producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 41 publications
5
68
0
Order By: Relevance
“…Bcl-2 is known to downregulate the apoptosis in human mononuclear phagocytes after infection with M. tuberculosis (16)(17)(18), and further, the downregulation of Bcl-2 is accompanied by upregulation of Bax, which has recognized apoptotic effects (16). Balcewicz-Sablinska et al (2) reported that IL-10 downregulates apoptosis by inhibiting the TNF-α production of the inoculated macrophages and by inducing the release of soluble TNF receptor type 2 from the macrophages, which leads to inactivation of TNF-α. It is considered from these reports and our data that in the early phase of infection with both M. tuberculosis H37Ra and H37Rv, the release of a relatively higher amount of TNF-α compared with that of IL-10 might be enhanced in the infected cells, which induces negative modulation of cysteine protease and Bcl-2 expression, leading the cells to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 is known to downregulate the apoptosis in human mononuclear phagocytes after infection with M. tuberculosis (16)(17)(18), and further, the downregulation of Bcl-2 is accompanied by upregulation of Bax, which has recognized apoptotic effects (16). Balcewicz-Sablinska et al (2) reported that IL-10 downregulates apoptosis by inhibiting the TNF-α production of the inoculated macrophages and by inducing the release of soluble TNF receptor type 2 from the macrophages, which leads to inactivation of TNF-α. It is considered from these reports and our data that in the early phase of infection with both M. tuberculosis H37Ra and H37Rv, the release of a relatively higher amount of TNF-α compared with that of IL-10 might be enhanced in the infected cells, which induces negative modulation of cysteine protease and Bcl-2 expression, leading the cells to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ATP-induced apoptosis in macrophages resulted in killing of M. bovis BCG (53,54). In addition, mycobacterial infection itself can induce apoptosis in infected macrophages (55). Ingestion of infected apoptotic macrophages by uninfected macrophages results in increased control of mycobacterial growth (56).…”
Section: Discussionmentioning
confidence: 99%
“…Patients and controls were selected from the California Collaborative Treatment Group 552 trial, which compared the efficacy of azithromycin to that of rifabutin with the combination of both drugs for the prevention of MAC infection (11). At entry, HIV-1-infected persons had CD4 counts of Ͻ100 cells/mm 3 and no history of MAC bacteremia. Disseminated MAC was determined on the basis of a positive culture of blood or another normally sterile site.…”
Section: Methodsmentioning
confidence: 99%